A psychological perspective of financial panic - Anat Bracha; Elke U. Weber (Federal Reserve Bank of Boston, 2012)
In spite of large number of financial crises, often depicted as episodes of financial panic, the notion of panic in financial markets is not very well understood. Many have argued that in order to understand financial crises, and in particular panic events, we need to go beyond classic economic arguments. This paper is an effort in that direction, in which we attempt to give a psychological account of panic and of panic in financial markets in particular, by discussing uncertainty, the desire for predictability and control, the illusion of control, and confidence. We suggest how one might incorporate these psychological insights into existing economic models.
Keywords: D03; E32; 330